Kategorie genologiczne ortogatunku, paragatunku i metagatunku - Bednarek, Zbigniew (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2013)
In the article, the canonical and differential characteristics of ortogenres, paragenres and metagenres are discussed, with an emphasis on the mechanism by which these journalistic and literary forms are generated, and the problem of documentary in relation (imitation, stylization), and an attempt is made to answer the question: what brings about ortogenres, paragenres and metagenres.